PENDEKATAN PENGAWASAN HORIZONTAL PADA ASPEK PERENCANAAN ANGGARAN DANA DESA SEBAGAI UPAYA PENCEGAHAN TINDAK KORUPSI DANA DESA (ANALISIS META-SINTESIS PADA PENGAWASAN DANA DESA) - Rizky Wulandari; Dina Natasari (UNIB Press, 2020)
The policy of the central government to provide sufficiently large amounts of village funds is a strategic step that must be responded by villages by promoting the principles of transparency and accountability. The principle of transparency and accountability in managing village funds is certainly the responsibility of the village head and his staff to the community. However, up to now cases of corruption and misuse of village fund management have increased. The role of supervision has become an urgent matter to be immediately corrected to prevent this. This research will identify the steps and things that must be done in horizontal supervision in preventing the corruption of village funds. This study aims to conduct an analysis with a meta-synthesis approach to supervision of village funds, to then form a conceptual framework of horizontal supervision of village fund planning as an effort to prevent corruption. This research uses a meta-synthesis approach using data in the form of journals, articles, and related references. The analysis process uses standard meta-analysis steps from determining problem questions to reporting results. The results of this study indicate that horizontal control by the village community is very necessary. Supervision in the aspect of village fund planning is not only from the financial side but also non-financial. Supervision starts from identifying needs, determining activities and preparing activity plans and budgets. Supervision in this aspect of the budget to ensure that village fund planning is by following community needs. Keywords:Supervision, Village Funds, Accountability, transparency, corruption